Quality of the thermal environment of urban courtyards in arid and semi-arid cities. Case of the city of Ouragla - Meriem, Gourari; Djamel, Alkama (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
This work deals with the quality of urban thermal environment in an arid context of the city of Ouargla, in the south-east of Algeria. The focus has long been on interior ambiences, while city producers are being asked, in the light of new sustainability data, to make more tangible improvements by ensuring acceptable standards in urban living. . The present work is part of this perspective and aims to improve the microclimatic quality of outdoor spaces. The study examines the response strategies in terms of climate adaptation research, especially in the summer period, and tries to evaluate the thermal regulation measures relating to criteria for attenuating energy heating due to intense diurnal solar radiation, which continues with a rise in temperature at night caused by heat loss under the effect of nocturnal radiation. And this by essentially taking into account the impact of the geometric parameters which consist of the profile of the built form expressed by the ratio of the height of the geometric form to its spatial extent defining different configurations at court in relation to different solar orientations. The objective is to assess whether such configurations can be the subject of models of organization of cities in an arid context. Field experimentation led to interesting results from a scientific point of view and likely to shed new light on the contribution of traditional urban form to passive strategies.